Two aelfric texts : the twelve abuses and the vices and virtues : an edition and translation of De duodecimo abusiuis and De octo uitiis et de duodecimo abusiuis /: the twelve abuses and the vices and virtues : an edition and translation of De duodecimo abusiuis and De octo uitiis et de duodecimo abusiuis. (2013) - Unknown
No abstract available